Pengaruh Dosis Pupuk N, P, dan K terhadap Kecernaan Secara In Vitro Rumput Gajah (Pennisetum purpureum) cv. Taiwan yang di Inokulasi CMA Glomus manihotis pada Lahan Bekas Tambang Batubara - Ifradi Ifradi; Evitayani Evitayani; A Fariani; L Warly; Suyitman Suyitman; S Yani; Emikasmira Emikasmira (Universitas Andalas, 2012)
This objective of the research was to investigated the digestibility of dry matter, organic matter and crude protein of elephant grass cv. Taiwan by in vitro technique. The method of research was using a Random Design Group with 5 treatments and 4 replications. The treatment A (100% N, P and K without CMA), treatment B (100% N, P, and K + 10gr of CMA), treatment C (75% N, P, and K + 10gr of CMA), treatment D (50% N, P, and K + 10gr of CMA) and treatment E (25% N, P, and K + 10gr of CMA), respectively. The results of the research showed that the effects of dry matter, organic matter and crude protein digestibility were not significantly (P<0.05) different between the treatments. The dry matter digestibility of elephant grass cv. Taiwan ranged from 53.47% to 57.72%, organic matter digestibility ranged from 57.66% to 63.75%, and crude protein digestibility ranged from 65.67% to 70.70%, respectively. It could be concluded that the given of 25% of N, P, and K + 10 gram of CMA glomus manihotis was better the digestibility on dry matter, organic matter and crude protein. Therefore, it means that the same value with fertilizer N, P, and K 100% without CMA.